(untitled) (Fiep Bulletin - online, 2014)
to revise in the literature the protocols used to evaluate the quality of the care given to venous ulcers patients at international context. Method: literature revision in nursing magazines at the scientific electronic sites BVS, PubMed and Web of Knowledge, from 2002 to 2006. Results: There were found articles with protocols and experiences of protocols use for care and evaluation of the nursing care given to patients with venous leg ulcers, showing that those protocols application result in better care, saves material and speed the wound cicatrization process. Conclusion: the protocol must be prepared by a multidisciplinary team, its use in care improves this care in all levels and it is useful in the evaluation of the quality of assistance given.